Sharia e-commerce in Indonesia: Sharia peer to peer lending - Yunika Sari (Center for Islamic Economics and Development Studies [P3EI], 2023)
Purpose – This article discusses the increasingly rapid development of the sharia e-commerce in Indonesia, focusing on FinTech peer to peer lending sharia.Methodology – This article uses qualitative methods and literature research (library research), with descriptive analysis techniques related to sharia FinTech lending in Indonesia, as well as a statutory approach, which is classified based on hierarchy and sources of law by comprehensive review.Findings – The theme of this article is that Islamic FinTech lending seeks to understand better how vital economic innovation is needed by society because FinTech lending is a new platform for fast and practical financial transaction services. However, although the Financial Services Authority (Otoritas Jasa Keuangan, OJK) has made FinTech lending regulations, no specific rules explicitly mention sharia FinTech lending. So there is still a possibility that some elements are different from Islamic sharia. So, of course, special regulations regarding sharia FinTech lending are urgently needed so that they follow Islamic laws. Implications – This article is useful, apart from adding to the repertoire, it can also be a means for studying financial service platforms in Indonesian society and can be used as reference material for further research in the same field.Originality – This article contributes to various financial service platforms to continue to improve and innovate in sharia-based financial activities, as well as provide an understanding to the wider community regarding the ease of accessing these sharia financial services